Whole chloroplast genome sequence of a subtropical tree Eriobotrya bengalensis (Rosaceae) - Xu, Jian (Mitochondrial DNA B Resour, 2020)
Eriobotrya bengalensis (Roxb.) is a subtropical plant under the family Rosaceae with high economic and medicinal value. The whole chloroplast genome of E. bengalensis was sequenced to better understand its phylogenetic position relative to other Rosaceae species. The total length of the E. bengalensis chloroplast genome was 159,270 bp, which was composed of a large single-copy (LSC) region of 87,362 bp, a small single-copy (SSC) region of 19,184 bp, and a pair of inverted repeats (IRs) with a length of 26,362 bp separated by LSC and SSC. The total G + C content of the whole chloroplast genome was 36.7%. Phylogenetic analysis of maximum likelihood (TVM + F+R2) was completed using 15 complete chloroplast genomes of Rosaceae species. The results of phylogenetic analysis show that sisterhood exists in E. bengalensis with nine other species of Eriobotrya.